2007
DOI: 10.1007/s00221-007-1173-z
|View full text |Cite
|
Sign up to set email alerts
|

Sensorimotor memory of weight asymmetry in object manipulation

Abstract: Using a precision grip-lifting task, we examined how sensorimotor memory for weight asymmetry transfers across changes in hand and object configuration. We measured object tilt when participants lifted a visually symmetric box with an offset centre of mass. Transfer was assessed after participants lifted the box 10 times, during which the large tilt observed in the first lift was reduced. Consistent with previous work of Salimi et al. (J Neurophysiol 84:2390-2397, 2000), we found that when the object was rotat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
22
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 21 publications
6
22
3
Order By: Relevance
“…When subjects perform subsequent lifts involving both a hand switch and object rotation (HS+OR), the object dynamics reverses in R E , but the torque remains unchanged in R I . It has been shown that, on the first trial after a change of manipulation context, subjects exhibit a large negative transfer in OR condition, but zero transfer in HS and HS+OR conditions [12]. However, this result differs from findings reported by studies of reaching movements using force fields [22].…”
Section: Introductioncontrasting
confidence: 57%
“…When subjects perform subsequent lifts involving both a hand switch and object rotation (HS+OR), the object dynamics reverses in R E , but the torque remains unchanged in R I . It has been shown that, on the first trial after a change of manipulation context, subjects exhibit a large negative transfer in OR condition, but zero transfer in HS and HS+OR conditions [12]. However, this result differs from findings reported by studies of reaching movements using force fields [22].…”
Section: Introductioncontrasting
confidence: 57%
“…These findings suggest that subjects started learning context B without any transfer from the previously learned context A, even when the 1-h break was long enough for the interference effect to decay to a minimum level. This phenomenon is consistent with those reported by previous studies (Bursztyn and Flanagan 2008;Fu and Santello 2012;Zhang et al 2010), which showed no task-level learning transfer from context A to B. Furthermore, here we demonstrate that lack of learning generalization in manipulation tasks was not due to lack of context cues or anterograde interference caused by learning a context immediately preceding the new context.…”
Section: Experiments 3: Time-dependent Interference On the Transfer Trialsupporting
confidence: 94%
“…Several lines of evidence support the latter scenario. Specifically, subjects are unable to fully transfer manipulative forces following an object rotation that changes the learned mapping between digit forces and object properties, for example, texture (Edin et al, 1992;Quaney and Cole, 2004) or mass distribution (Salimi et al, 2000(Salimi et al, , 2003Bursztyn and Flanagan, 2008;Albert et al, 2009;Ingram et al, 2010;Zhang et al, 2010).…”
Section: Are Learned Manipulations Always Transferable?mentioning
confidence: 99%
“…Interestingly, however, there are instances where the congruence between manipulation task and hand frame of reference can be broken by changing the hand position relative to the object without interfering with transfer of learned manipulation (Quaney and Cole, 2004;Bursztyn and Flanagan, 2008). These two studies, together with the above-cited work, suggest that the interference to learning transfer is not caused by the lack of congruence between hand and manipulation frames of reference per se, but rather by the inability of the CNS to mentally rotate the action as a function of the object's new orientation relative to the hand.…”
Section: Are Learned Manipulations Always Transferable?mentioning
confidence: 99%
See 1 more Smart Citation